Herpes zoster oftalmikus dengan komplikasi okular: Laporan kasus - Desak Nyoman Trisepti Utami; Luh Made Mas Rusyati; Prima Sanjiwani Saraswati Sudarsa (Intisari Sains Medis, 2021)
Background: Herpes zoster ophthalmicus occurs in 10-20% of cases of herpes zoster. Herpes zoster ophthalmicus occurs when the human herpes virus type 3 reactivates the first division of the trigeminal nerve, which is also called the ophthalmic division. In some patients, it may show ocular involvement.Case: A 60 years old male patient came with swelling and wounds on the left forehead and around the left eye. Initially appear as watery spots and accompanied by pain. The pain felt like being stabbed, hot like burning sensation. The patient had chickenpox as a child. In the dermatological status of the superior palpebra, frontalis and left parietalis, multiple erythema patches were seen with multiple erosions. It appears that the lesion is unilaterally distributed according to the dermatome of the trigeminal cranial nerve of the left ophthalmic branch. Gram examination on erosive lesions showed the presence of 1-5 leukocytes / large field of view with Gram positive cocci and no Gram negative rods. The patient was diagnosed with herpes zoster ophthalmicus left with secondary infection. Consultation to ophthalmology division revealed left ocular herpes zoster ophthalmic (blepharoconjunctivitis), corneal erosions, iridoplegia and mature senile cataracts. The patient discharged on the fifth day. On the 11th day, complaints of watery eyes, swelling and eye discharge were gone.Conclusion: A case of herpes zoster ophthalmicus in old age with ocular complications and secondary infection was reported. For erosional lesions, open compresses was applied with NaCl and sodium fusidate cream. Patients respond well to therapy. Latar Belakang: Herpes zoster oftalmikus terjadi pada 10-20% dari kasus herpes zoster. Herpes zoster oftalmikus terjadi ketika human herpes virus tipe 3 mengalami reaktivasi pada divisi pertama dari saraf trigeminalis, yang disebut juga divisi oftalmik. Pada beberapa pasien, dapat menunjukkan keterlibatan okular.Laporan Kasus: Pasien laki-laki, usia 60 tahun datang dengan keluhan bengkak dan luka pada dahi kiri serta area sekitar mata kiri. Awalnya muncul berupa bintik-bintik berair dan disertai nyeri. Nyeri dirasakan seperti ditusuk-tusuk, panas seperti terbakar, dan mata terasa seperti tertarik. Pasien pernah menderita penyakit cacar air pada saat kanak-kanak. Pada status dermatologis palpebra superior, frontalis dan parietalis sinistra tampak patch eritema multipel dan pada beberapa tempat disertai erosi multipel. Tampak lesi terdistribusi secara unilateral sesuai dermatom nervus kranial trigeminus cabang oftalmikus sinistra. Pemeriksaan Gram pada lesi erosi menunjukkan adanya leukosit 1-5/lapang pandang besar, ditemukan adanya kokus Gram positif dan tidak didapatkan batang Gram negatif. Pasien didiagnosis dengan herpes zoster oftalmikus sinistra disertai infeksi sekunder. Konsultasi pada bagian mata didapatkan okuli sinistra herpes zoster optalmika (blefarokonjungtivitis), erosi kornea, iridoplegia dan katarak sinilis matur. Pasien dipulangkan pada hari kelima perawatan. Pada hari ke 11, Keluhan mata berair, bengkak dan kotoran mata sudah tidak ada.Simpulan: Telah dilaporkan sebuah kasus herpes zoster oftalmikus pada usia tua dengan komplikasi okular dan didapatkan juga infeksi sekunder. Pada lesi erosi diberikan kompres terbuka dengan NaCl dan krim natrium fusidat. Pasien memberikan respon yang baik dengan terapi.